BUR1 and BUR2 Encode a Divergent Cyclin-Dependent Kinase–Cyclin Complex Important for Transcription In Vivo - Yao, Sheng (American Society for Microbiology, 2000)
BUR1 and BUR2 were previously identified by a genetic selection for mutations that increase transcription from basal promoters in vivo. BUR1 encoded a putative protein kinase with greatest similarity to members of the cyclin-dependent kinase (CDK) family, although that similarity was not sufficient to classify it as a CDK. It was also not known whether Bur1 activity was cyclin dependent and, if so, which cyclins stimulated Bur1. The molecular cloning and characterization of BUR2 presented here sheds light on these issues. Genetic analysis indicates that BUR2 function is intimately related to that of BUR1: bur1 and bur2 mutations cause nearly identical spectra of mutant phenotypes, and overexpression of BUR1 suppresses a bur2 null allele. Biochemical analysis has provided a molecular basis for these genetic observations. We find that BUR2 encodes a cyclin for the Bur1 protein kinase, based on the following evidence. First, the BUR2 amino acid sequence reveals similarity to the cyclins; second, Bur1 and Bur2 coimmunoprecipitate from crude extracts and interact in the two-hybrid system; and third, BUR2 is required for Bur1 kinase activity in vitro. Our combined genetic and biochemical results therefore indicate that Bur1 and Bur2 comprise a divergent CDK-cyclin complex that has an important functional role during transcription in vivo.